Pengaruh Pendidikan Agama Islam dalam Keluarga dan Budaya Religius Sekolah terhadap Akhlak Karimah Peserta Didik MTs Wathoniyah Japurabakti Kecamatan Astanajapura Kabupaten Cirebon - muhammad heriyanto (Permata : Jurnal Pendidikan Agama Islam, 2020)
This study aims to answer the problem formulation as follows: (1) To what extent does Islamic religious education in the family affect the morality of the students of MTs Wathoniyah Japurabakti? (2) To what extent does the school's religious culture influence the morality of the MTs Wathoniyah Japurabakti students? (3) Does the extent of Islamic religious education in the family and religious culture of schools affect the morality of the students of MTs Wathoniyah Japurabakti? This research was conducted with a quantitative approach that is descriptive correlational that is looking for relationships and influences of the independent variables of Islamic religious education in the family (X1), school religious culture (X2) with the dependent variable morals karimah (Y), both individually and together, The results showed that each independent variable and the dependent variable had a positive correlation and significant influence, namely Islamic religious education in the family (0.456) and religious school culture (0.373). Together there is a significant relationship between Islamic religious education in the family with the religious culture of the school and the moral mercy with an R value of 0.495, R2 of 0.245. This means that the percentage contribution of the influence of the independent variable (Islamic religious education in the family and religious culture of the school) to the dependent variable (morals of students) is 24.5%. Abstrak Penelitian ini bertujuan untuk menjawab rumusan masalah sebagai berikut: (1) Sejauh mana pendidikan agama Islam dalam keluarga berpengaruh terhadap akhlak karimah peserta didik MTs Wathoniyah Japurabakti? (2) Sejauh mana budaya religius sekolah berpengaruh terhadap akhlak karimah peserta didik MTs Wathoniyah Japurabakti? (3) Apakah Sejauh mana pendidikan agama Islam dalam keluarga dan budaya religius sekolah berpengaruh terhadap akhlak karimah peserta didik MTs Wathoniyah Japurabakti?.Penelitian ini dilakukan dengan pendekatan kuantitatif yaitu deskriptif korelasional yaitu mencari hubungan dan pengaruh variable independen pendidikan agama Islam dalam keluarga (X1), budaya religious sekolah (X2) dengan variabel dependen akhlak karimah (Y), baik secara sendiri-sendiri maupun bersama-sama.Hasil penelitian menunjukkan bahwa masing masing variabel independen dan variabel dependen memiliki korelasi positif dan pengaruh signifikan yaitu pendidikan agama Islam dalam keluarga (0,456) dan budaya religious sekolah (0,373). Secara bersama-sama terdapat hubungan yang signifikan antara pendidikan agama Islam dalam keluarga dengan budaya religious sekolah dengan akhalk karimah dengan nilai R sebesar 0,495, R2 sebesar 0,245. Ini berarti Bahwa persentase sumbangan pengaruh variable independen (pendidikan agama Islam dalam keluarga dan budaya religious sekolah) terhadap variable dependen (akhlak karimah peserta didik) sebesar 24,5%.